The Effect of Managerial Coaching Skills on Team-Level Architectural Knowledge and Team Performance Moderated by Manager Learning Goal Orientation - Hafidz, Gilang Pratama; Nurdiansyah, Erfian (International Journal of Economics (IJEC), 2024)
Managerial coaching skills play an important role in human resource strategy which can be utilized by companies by providing the impact of training to broaden employ-ee perspectives and improve employee performance. The goal of this study is con-ducted to investigate the connection between Managerial coaching skills to team-level architectural knowledge and team performance. Quantitative research is used in this field with the technique purposive sampling was used, and questionnaires were handed out to 120 permanent employee respondents at Indonesian sharia non-banking financial institutions aged 23-50 years and are in the Tangerang Regency area. The primary data was analyzed using the method of Structural Equation Mod-eling (SEM). The three assumptions put forth are supported by the study's findings, which also show that team-level architectural knowledge has the biggest direct impact on team performance. Then managerial coaching skill has the greatest indirect effect on relationships between team-level architectural knowledge with team performance. This research contributes to companies in maintaining and improving team performance looking at several factors, team-level architectural knowledge is formed from optimal and measurable managerial coaching skill. The researcher advises broadening the study's scope and seeking objects in related domains as subsequent investigation.